Overcoming Drought in India : Adaptation Strategies for the State of Andhra Pradesh - World Bank (Washington, DC, 2012)
The study objectives were designed to enhance the state's capacity to assess long-term effects of drought and increase resilience to drought risks at state, district, and community levels. The process for development of study objectives featured extensive consultation with affected sectors, and with state and national programs that aim to address the effects of drought. The study aimed to: (i) develop a framework for simulating long-term impacts of drought in drought-prone areas and at state levels; (ii) conduct risk assessments of the impacts under different scenarios; and (iii) assist the Government of Andhra Pradesh (GoAP) in development of a strategy for adapting to frequent drought and water deficits. During the study, a model was developed as a powerful tool for thorough drought risk assessments and for investigation of risk coping strategies and climate scenarios on crop yield and production. The model was calibrated using local farming practices and crop selection (that is, rice, maize, jowar (sorghum), sunflower, and groundnut,) in the eight selected districts. The report presents results at the district level. Challenges in determining the economic impacts included: the slow onset of droughts that spread over long periods and large areas; the significant indirect losses; the need to link local impact analysis with statewide analysis; and the linkages between the different sectors and subsectors of the economy, the flow of goods and services and employment.